Engineering Intracellular Delivery Nanocarriers and Nanoreactors from Oxidation-Responsive Polymersomes via Synchronized Bilayer Cross-Linking and Permeabilizing Inside Live Cells - Deng, Zhengyu; Qian, Yinfeng; Yu, Yongqiang; Liu, Guhuan; Hu, Jinming; Zhang, Guoying; Liu, Shiyong (Journal of the American Chemical Society, 2016)
Reactive oxygen species (ROS) and oxidative stress are implicated in various physiological and pathological processes, and this feature provides a vital biochemical basis for designing novel therapeutic and diagnostic nanomedicines. Among them, oxidation-responsive micelles and vesicles (polymersomes) of amphiphilic block copolymers have been extensively explored; however, in previous works, oxidation by ROS including H2O2 exclusively leads to microstructural destruction of polymeric assemblies. For oxidation-responsive polymersomes, fast release of encapsulated hydrophilic drugs and bioactive macromolecules will occur upon microstructural disintegration. Under certain application circumstances, this does not meet design requirements for sustained-release drug nanocarriers and long-acting in vivo nanoreactors. Also note that conventional polymersomes possess thick hydrophobic bilayers and compromised membrane permeability, rendering them as ineffective nanocarriers and nanoreactors. We herein report the fabrication of oxidation-responsive multifunctional polymersomes exhibiting intracellular milieu-triggered vesicle bilayer cross-linking, permeability switching, and enhanced imaging/drug release features. Mitochondria-targeted H2O2 reactive polymersomes were obtained through the self-assembly of amphiphilic block copolymers containing arylboronate ester-capped self-immolative side linkages in the hydrophobic block, followed by surface functionalization with targeting peptides. Upon cellular uptake, intracellular H2O2 triggers cascade decaging reactions and generates primary amine moieties; prominent amidation reaction then occurs within hydrophobic bilayer membranes, resulting in concurrent cross-linking and hydrophobic-to-hydrophilic transition of polymersome bilayers inside live cells. This process was further utilized to achieve integrated functions such as sustained drug release, (combination) chemotherapy monitored by fluorescence and magnetic resonance (MR) imaging turn-on, and to construct intracellular fluorogenic nanoreactors for cytosolic thiol-containing bioactive molecules.